2016
DOI: 10.1186/s12879-016-1669-x
|View full text |Cite
|
Sign up to set email alerts
|

Results from the centers for disease control and prevention’s predict the 2013–2014 Influenza Season Challenge

Abstract: BackgroundEarly insights into the timing of the start, peak, and intensity of the influenza season could be useful in planning influenza prevention and control activities. To encourage development and innovation in influenza forecasting, the Centers for Disease Control and Prevention (CDC) organized a challenge to predict the 2013–14 Unites States influenza season.MethodsChallenge contestants were asked to forecast the start, peak, and intensity of the 2013–2014 influenza season at the national level and at an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
198
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(201 citation statements)
references
References 26 publications
3
198
0
Order By: Relevance
“…A nice summary the results of such approaches in providing actual predictions for the 2013-2014 flu season in the USA is detailed in Ref. [737].…”
Section: Social Media Based Methodsmentioning
confidence: 99%
“…A nice summary the results of such approaches in providing actual predictions for the 2013-2014 flu season in the USA is detailed in Ref. [737].…”
Section: Social Media Based Methodsmentioning
confidence: 99%
“…Early identification of the timing and intensity of the annual seasonal epidemic of influenza is useful to inform public health planning and response. To determine if reasonably accurate forecasts can be made during flu season, the Centers for Disease Control and Prevention (CDC) organized a challenge to predict the 2013-2014 United States influenza season (8). Findings indicated that flu forecasting can yield reasonably accurate estimates of the start, peak, and intensity of the influenza season.…”
Section: The Expanding Use Of Surveillance Systemsmentioning
confidence: 99%
“…Influenza can be fatal to those in patients with poor weak immunity (mostly infants, and young children, and the elderly people). The difference between the two is that common cold is caused by rhinovirus, whereas influenza is caused by influenza is caused by influenza virus the influenza virus causes influenza [14][15][16][17][18], as a comparison of these illnesses is listed in Table I. Comparison of the differences of the common cold and influenza.…”
Section: Influenza Investigationmentioning
confidence: 99%